Acute Hypokalemia Related with Thyrotoxicosis Periodic Paralysis: A Case Report - Kadek Reisya Sita Damayanti; Rizaldy Taslim Pinzon (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2024)
Introduction : Hypokalemia paralysis is a rare condition. Thyrotoxic periodic paralysis (TPP) is a condition of hyperthyroidism characterized with acute muscle weakness and hypokalemia. TPP is commonly found in young Asian male. TPP is an uncommon clinical entity and might be a life threatening complication of thyrotoxicosis. We report a rare case of TPP with ECG abnormality related with severe hypokalemia. Case Report : A-21-year old Javanese male was presented to emergency department with acute onset of lower bilateral extremities weakness with proximal muscle predominant. Weakness progressed to his bilateral upper limb. Patient denied any significant trauma, vomiting, diarrhea, chest pain. Patient was fully conscious. Neurological examination revealed four limb weakness (lower limb muscle strength 2 from 5 scale MRC), diminished deep tendon reflexes, and intact sensory. Laboratory were remarkable for severe hypokalemia of 1.86 mEq/L. Further tests showed low TSH (0.022 mU/L), increased FT4 (23,68 mmol/L). ECG test showed abnormality related with hypokalemia. Thyroid ultrasound revealed multiple thyroid swelling, mass, and calcification. Patient was admitted to ICU and administered with 25mEq Potassium IV. Hypokalemia resolved after 3 days (Serum Potassium 3.76 mEq/L), followed by normal ECG feature without any AV block. He was discharged without any neurological abnormaliy. Conclusion : We report a rare case of acute onset paralysis and markedly low potassium level and high free T4 in previously health Asian male. This case highlights the paralysis related with hyperthyroidism that resolved completely following potassium replacement. Keywords: hypokalemia; paralysis; hyperthyroid; thyrotoxicosis periodic paralysis